Microbial and extracellular polymeric substance dynamics in arid"“zone temporary pan ecosystems - Bute, Tafara Frank (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Microbial communities of bacteria, viruses, algae, protozoans and fungi participate profoundly in aquatic systems, particularly in mediating processes such as primary production, decomposition, and biogeochemical cycles. In addition, microbiomes produce extracellular polymeric substances (EPS) which encompass a hydrated exopolymer mainly constituted of carbohydrates and proteins. The exopolymer aid proliferation and persistence of biofilms on their resident surfaces. There is however paucity of data on functional diversity of microbiomes in arid zone temporary wetlands with previous research having mainly focused on permanent systems in the northern hemisphere. In the face of ongoing climatic changes and anthropogenic threats to wetlands, it is imperative to assess the health status of aquatic systems in relation to microbial productivity dynamics. In this thesis, colorimetric methods and sequence"“based metagenomics were conducted to quantify microbial EPS production and bacterial metagenome functions, respectively. This study was conducted in Khakhea"“Bray region (North"“West, South Africa) in June 2021 and January 2022 with a focus on evaluating microbial patterns of distribution between seasons (i.e., Dry and Wet) and varying depth i.e., deepest zones (Deep), intermediate depth (Mid) and shallowest regions (Edge). Additionally, potential relationships between EPS and either water content or organic matter content (OM content) were evaluated. In this study it was hypothesized that wet phases and deeper zones will have high EPS production and support more functions in comparison to shallowest regions and dry phases. Carbohydrates and proteins were quantified using the Dubois method and modified Lowry procedure, respectively. Carbohydrates generally occurred in higher proportions than proteins, suggesting that EPS found in these systems was largely diatom produced. The wet phases (wet season and inundation periods) supported more EPS production compared to the dry phases. The results of principal components analysis (PCA) and Spearman's correlations suggested that EPS was highly correlated with sediment water content among other assessed variables. No significant associations were established between EPS and organic matter content. Spatial distribution of EPS demonstrated similar patterns between the deepest (Deep) and the intermediate depth zones (Mid) however the shallow regions (Edge) had significantly lower concentrations. Bacterial characterization was established by amplification of the 16S rRNA gene using illumina"“sequencing protocol. Enzyme functions associated with biogeochemical pathways were predicted in PICRUSt2 bioinformatics pipeline. A total of 15 042 Unique Amplicon Sequence Variants (ASVs) were observed to be affiliated to 51 bacterial phyla and 1 127 genera. All top genera had commonality in heat tolerance. Firmicutes, dominated at phyla level with 59 % (mean Â± sd, 19 Â± 13 %) relative abundance followed by Actinobacteria and Proteobacteria both at 34 % (18 Â± 7 %) and (18 Â± 6 %), respectively. Microbial diversity matrices highlighted significant differences in beta diversity more than alpha diversity. Bacterial microbiomes were more distinct between seasons compared to within season, suggesting that functions were seasonally driven. These findings were supported by highest rates of denitrification, carbohydrate degradation and EPS production by core microbiomes in the wet season as compared to low rates of nitrogen mineralisation, carbon fixation and nitrification in the dry season. The present findings represent a first attempt in evaluating sequence"“based metagenomics in semi"“arid southern African temporary pan ecosystem. Both microbial EPS and bacterial functional potential were highly driven by water availability, with highest rates mainly associated with maximum inundation compared to dry states of pans. It can therefore be suggested that extended dry periods are threatening to microbially mediated processes in temporary wetlands, with implications to loss of biodiversity due to desiccation resulting in poor nutrient cycling.
Keywords: Extracellular polymeric substances; Biofilms; Vernal pools; Microbiomes; Sediment-water interface